Intellectual Property Rights Protection Function in Resolving Copyright Disputes - Rachmad Abduh; Fajaruddin Fajaruddin (International Journal Reglement & Society (IJRS), 2021)
Copyright is the exclusive right of the creator or Copyright Holder to regulate the use of the results of casting certain ideas or information. Basically, copyright is the “right to copy a work”. Copyrights can also enable such holders to restrict unauthorized copying of creations from. In general too, copyright has a certain specified validity period. Based on the problems that often occur in copyright, there are mutual claims of creations that always appear at the Director General of Intellectual Property Rights, Menkum HAM, which ultimately in the Commercial Court, this is due to the absence of mandatory registration of works. Law Number 28 of 2014 explains